Oil recovery from a fluctuating water table. (16th September 2016) - Kuo, T.; Chen, Y.; Lin, C.; Chen, J.
ABSTRACT: Oil recovery in an unconfined aquifer was affected by precipitation and a fluctuating water table at the 322.5 K site in Taiwan. An immiscible displacement model was applied to quantify the effect of precipitation on oil recovery. This study also investigated a method to determine the field-average residual oil saturation by simulating the observed cumulative oil recovery with time.